Desenvolvimento de fêmeas leiteiras mediante o uso de leite cru ou sucedâneo - Zanotti, Josinaldo (2015)
The aim of this study was to evaluate the performance and economical viability of dairy females in lactating phase receiving raw milk or commercial substitute. The experiment was carried out in dairy farms in Paraná southwest region. Thirty-two new-born calves were used until the weaning, sixteen in each treatment. After weaning fourteen calves were used, seven in each treatment. For both treatments black and white Holstein animals were used. The experiment was carried out from March/2012 to August/2013. Two treatments were evaluated, one feeding the calves with raw milk and the other based on milk substitute. Weight gain, chest girth, abdominal girth, withers height, rump height, rump length, rump width, rump girth, and animal body width were measured. No significant differences (p>0.05) were observed for all the evaluated morphological variables. Although the cost of the substitute is inferior during lactation, the producer has to pay attention to the necessary equipment and the time taken for the proper preparation and animal feeding. The use of milk substitute ensures good performance and morphological development when compared to using raw milk.